Total Synthesis of (+)-Greek Tobacco Lactone - Siitonen, Juha H.; Pihko, Petri M. (Synlett, 2014)
An enantioselective, protecting-group-free, total synthesis of (+)-Greek tobacco lactone has been achieved by using an organocatalytic Mukaiyama–Michael reaction and a stereospecific oxa-Michael reaction as key steps.
Keywords: total synthesis; natural products; Michael additions; ring closure; cyclizations